Gambaran Bendungan Asi Pada Ibu Nifas Berdasarkan Karakteristik - Aprilina, Aprilina; Jasmi, Jasmi; Noviyanti, Asri; Setiawati, Desy; Habiba, Habiba (JKM : Jurnal Keperawatan Merdeka, 2025)
Background: Breast milk dams are an abnormal condition, painful because the breasts are swollen, without edema, the nipples and areola look tight, the skin is shiny and looks red. If the entire breast is pressed/squeezed it will feel hard. Purpose: to find out the description of breast milk dams in postpartum mothers based on maternal characteristics (education, occupation, age and parity) at the Habiba Independent Midwife Practice Place (TPMB) area Lubuk Linggau City in 2024.. Methods: : This type of research is a quantitative descriptive research type. Using a total sampling technique, which means a sampling technique where the number of samples is the same as the population. So the sample in this study was 236 breastfeeding mothers., Results: The results of statistical test research using univariate analysis (descriptive analysis) were obtained. Most of the respondents were highly educated (high school, bachelor's degree) with a percentage of 57.2%, some respondents worked with a percentage of 63.6%, most of the respondents were aged 20 - 35 years with a percentage of 73.3% and Most of the respondents were mothers with multiparous parity/mothers who had more than 1 child with a percentage of 61.9%..Conclusion: The results of statistical test research using univariate analysis (descriptive analysis) were obtained. Most of the respondents were highly educated (high school, bachelor's degree) with a percentage of 57.2%, some respondents worked with a percentage of 63.6%, most of the respondents were aged 20 - 35 years with a percentage of 73.3% and Most of the respondents were mothers with multiparous parity/mothers who had more than 1 child with a percentage of 61.9%.